2014
DOI: 10.1016/j.bbamcr.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of microRNA-128a expression contributes to the apoptosis-resistance of human T-cell leukaemia Jurkat cells by modulating expression of Fas-associated protein with death domain (FADD)

Abstract: Increased expression of miR-128a is often observed in acute lymphoblastic leukaemia (ALL) compared with its expression in acute myeloid leukaemia (AML). The objective of this study was to investigate the role of miR-128a, especially that in the Fas-signalling pathway, in T-cell leukaemia cells. The role of miR-128a in Fas-mediated apoptosis was examined by using Fas-activating antibody (CH-11)-susceptible Jurkat cells and -resistant Jurkat/R cells. Whereas ectopic expression of miR-128a conferred Fas-resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…Although to the best of our knowledge chromosomal aberrations or mutations specifically affecting miR-128 loci have not been reported so far, there is evidence that miR-128-3p expression could be affected by perturbed epigenetic regulation [hypomethylation of miR-128 promoter(s)] in T-ALL cells. 25,30 Finally, miR-128 over-expression was also demonstrated to result in increased resistance of Jurkat/R (T-ALL) cells to Fas-mediated apoptosis, 30 indicating that miR-128(-3p) can have oncogenic properties in T-ALL cells. In line with these studies, we have demonstrated, using T-ALL mouse models, that miR-128-3p can indeed have oncogenic properties in T-ALL development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although to the best of our knowledge chromosomal aberrations or mutations specifically affecting miR-128 loci have not been reported so far, there is evidence that miR-128-3p expression could be affected by perturbed epigenetic regulation [hypomethylation of miR-128 promoter(s)] in T-ALL cells. 25,30 Finally, miR-128 over-expression was also demonstrated to result in increased resistance of Jurkat/R (T-ALL) cells to Fas-mediated apoptosis, 30 indicating that miR-128(-3p) can have oncogenic properties in T-ALL cells. In line with these studies, we have demonstrated, using T-ALL mouse models, that miR-128-3p can indeed have oncogenic properties in T-ALL development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that FAS-associated death domain (FADD) protein is a key adaptor in the death-receptor-mediated apoptosis [24]. In this context, the death receptor FAS is activated upon the binding of FAS ligand (FASL) and cytoplasmic FADD via its death domain (DD), which in turn further recruits and activates procaspase-8 to initiate an induction of apoptosis [24, 25]. To assess an involvement of extrinsic signaling in CPS- or M. ovipneumoniae- induced cell apoptosis, the expression of FAS/FASL signaling-related proteins, including FADD, FAS, FASL, and cleaved-caspase-8 was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Nami et al [94] reported that FADD played a role in mediating miRNAs by regulating the fas-mediated apoptosis signaling pathway and found that demethylation of the promoter region for R3H domain containing 1 and consequent up-regulation of miR-128a following the fas stimulation inhibited FADD induction by directly binding to its 3′-UTR, resulting in resistance to fas-mediated apoptosis in leukemia cells. Ectopic expression of miR-128a conferred fasresistance in Jurkat cells, as was evidenced by decreased cell viability and increased PARP-1 cleavage, while antagonizing the expression of miR-128a sensitized Jurkat/R cells to fas-induced apoptosis, as represented by increased viability and decreased PARP-1 cleavage.…”
Section: Mirnas Regulate Cell Apoptosis-related Proteinsmentioning
confidence: 98%